Featherback (Chitala ornata) Skin Protein Hydrolysate: Antioxidant Activity, Amino Acid Composition, Foaming and Emulsifying Properties - Tam D. L. Vo; Khang L. Duong; Anh N. Q. Nguyen; Bao C. Vo; Minh C. Tran; Hoa G. Tran; Tien T. Nguyen; Hung H. Lam; An T. H. Nguyen (Chemical Engineering Transactions, 2023)
In this study, featherback (Chitala ornata) skin was used to generate an antioxidant protein hydrolysate with foaming and emulsifying properties. Hydrolysates were obtained by using Alcalase preparation, a skin:water ratio of 1:2 (w/v), a pH 7.5, 55 °C, an enzyme:substrate ratio of 80 U/g protein, and a 5 h hydrolysis time. In terms of antioxidant activity, the hydrolysate showed 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity and 2,2'-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging capacity at 3.00 mg/mL and 1.82 mg/mL as the inhibitory concentration of 50 % free radicals (IC50), which was 731.71 and 27.58 folds higher than those of vitamin C, in order. It also displayed moderate foaming property, with its foaming capacity (FC) and foaming stability (FS) being 1.08 - 1.55 and 1.19 - 2.89 times lower than those of albumin, in that order. In contrast, the hydrolysate exhibited great emulsifying properties with an emulsifying activity index (EAI) and emulsifying stability index (ESI) comparable to those of sodium caseinate at pH 3-8. The hydrolysate contained a high concentration of lipophilic amino acids (AAs) (87.28 % of total AA content). As a result, featherback skin hydrolysate may be considered as a versatile ingredient for the development of natural antioxidants with technological capabilities.